The Role of Positive Health Behaviors in the Relationship Between Early Life Stress and Migraine. Issue 6 (22nd April 2020) - Hammond, Nicole G.; Colman, Ian
Abstract : Background: The use of diet and physical activity in alleviating the burden of migraine is unclear, therefore, more scientific study on the role of positive health behaviors in migraine management is needed. Objective: To explore the potential moderating influence of positive health behaviors on the early life stress‐migraine relationship in a sample of the Canadian adult population. Methods: This study used data from the 2011‐2012 Canadian Community Health Survey – Annual Component, a National cross‐sectional survey. Adults ≥18 years of age residing in British Columbia were surveyed about stressors experienced as children/teenagers (eg, parental divorce and substance abuse exposure). Migraine was self‐report of health‐professional diagnosis. Positive health behaviors were measured using an index of transportation and leisure time physical activity, and self‐reported frequency of vegetable and fruit consumption. Population survey weights were employed throughout and analytic models were adjusted for known confounders (nunweighted  = 11, 910). Results: The weighted prevalence of migraine was 9.7% (95% CI: 9.1%, 10.2%). Odds of migraine increased as number of stressors increased: 1 early life stressor (OR = 1.18, 95% CI: 1.01, 1.39), and ≥ 2 early life stressors (OR = 1.51, 95% CI: 1.29, 1.76), compared to no stress. There was evidence of effect modification by physical activity ( χ 2 (4) = 16.02, P  < .001). The association between 1 early life stressor and migraine was lower for those who were physically active (moderately active: OR = 1.20, 95% CI: 0.90, 1.61; active: OR = 0.82, 95% CI: 0.61, 1.11). This difference was not apparent for those who experienced 2 or more early life stressors (moderately active: OR = 1.67, 95% CI: 1.28, 2.17; active: OR = 1.55, 95% CI: 1.21, 1.99). Across all levels of early life stress, physically active respondents had lower odds of migraine than moderately active respondents. There was no effect modification by vegetable, fruit, and total fruit/vegetable consumption. Conclusions: Stressors experienced early in life are associated with migraine, and physical activity may ameliorate this relationship, particularly for those with exposure to a minimal level of early life stress. A higher dose of physical activity may yield greater benefit than a less intensive dose (ie, moderate activity level). However, the cross‐sectional nature of this study precludes us from inferring causality, and future investigation requires prospectively collected data.